Thermal Stability and Flame Retardancy of a Cured Trifunctional Epoxy Resin with the Synergistic Effects of Silicon/Titanium - Cheng, Zhipeng (ACS Omega, 2020)
[Image: see text] An amino curing agent containing silicon/titanium flame-retardant elements (STCA) based on (3-aminopropyl)triethoxysilane (APTES) and tetrabutyl titanate was successfully prepared. The thermal decomposition and flame-retardant properties of a STCA-cured trifunctional epoxy resin, which was facilely synthesized by 1,1,1-tris(4-hydroxyphenyl)ethane and epichlorohydrin via a two-step method, were compared with those of another amino curing agent containing silicon (SCA) based on APTES and methyltrimethoxysilane. The structures of STCA and SCA were characterized by Fourier transform infrared (FT-IR), (29)Si NMR, and Raman spectroscopies. The STCA-cured thermoset not only had good thermal stability with an initial decomposition temperature of 344.8 °C and a char yield of 52.7% at 800 °C but also exhibited the overall improvement of flame-retardant properties. V-0 rating was achieved using the UL-94 test, and the value of limiting oxygen index reached 33.8%. From the thermogravimetry–infrared test, the yield of pyrolysis products of the STCA-cured thermoset was significantly decreased, indicating the lower toxicity in contrast to the SCA-cured thermoset. Flame-retardant performances were also investigated using the cone calorimetry test, and the flame retardancy mechanism was studied using scanning electron microscopy, FT-IR, and energy-dispersive spectrometry. The results indicate that the introduction of silicon/titanium to the system reveals the synergistic effects to promote the formation of an intumescent, sufficient, and compact char layer during combustion, which could effectively prevent heat, oxygen, and flame from penetrating into the interior structure, and lead to the retardance of further combustion.